Estudo teórico computacional de suspensões coloidais de nanopartículas em solventes orgânicos - Guedes Sobrinho, Diego (Universidade Federal de São Carlos, 2013)
In this work, were studied nanoparticles colloidal systems ZrO2 were using coarse grained models in order to observe the influence of the interaction potential between nanoparticles and the solvents in the system coloidal structure at chemical equilibrium. The molecular dynamics (MD) method was applied to propagate the system trajectories from an optimized initial structure. The interaction energy values allowed the evaluate of which systems reached the colloidal stability and which converged to aggregates with different morphologies just by self-organization mechanisms. The analysis based of the radial distribution function allowed us to relating the nanoparticles superficial faces with the morphologies of aggregates for the correlations peak positions. The radial pair distribution plots and the average of interaction energy determined the interaction potential effect of the solvent in the colloidal systems structure at equilibrium. The colloidal stability was favored when the interaction potential of nanoparticles was equivalent to the interaction potential of the solvent, i.e., almost attractive nanoparticles in almost attractive solvent and attractive nanoparticles in attractive solvents. In other hand, the variation of solvent s interaction potential, using almost attractive nanoparticles in attractive solvent and attractive nanoparticles in almost attractive solvent, leaded systems to form nanoparticles aggregates with different morphologies, depending on the interaction between nanoparticles. Almost attractive nanoparticles formed a nanobunch, whereas attractive nanoparticles formed a nanorod. Gibbs energy of the nanoparticles aggregation process in each system was calculated, which indicated concordance between the thermodynamic of the aggregation process or of colloidal stabilization and the equilibrium systems obtained by molecular dynamic.
The computational theoretical study of nanoparticles colloidal suspension in organic solvents
Keywords: Física e química teórica; Nanopartículas (coarsegrained); Dinâmica molecular; Distribuição radial de pares; Potencial de força média; CIENCIAS EXATAS E DA TERRA::QUIMICA